PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 12 PADANG - Nopi Andriani, Agusti; Zulfaneti, Zulfaneti; febriana, Rina (Pendidikan Matematika, 2014)
ABSTRACTThe background of this research is based on the students understanding of mathematical concept which low and student do not usual to discuss study in group also. The purpose of this research is to know whether students understanding of mathematical concept by applying cooperative learning type Student Teams Achievement Division (STAD) better than students understanding of mathematical concept by applying conventional learning at class X SMAN 12 Padang. The kind of this research is experimental research which use randomly research design to subject. The population of this research is student class X SMAN 12 Padang. Class X.3 as experimental class and X.4 as control class. The instrument used in this research is final test of result mathematical concepts  understanding with reability test is The technique of data analysis used is t-test. Based  on the final test mathematics value student at both sample classes are gotten and ,it means that the hypothesis can be accepted because . It can be concluded that students understanding of mathematical concept by applying cooperative learning type Students Teams Achievement Division (STAD) better than students understanding of  mathematical concept by applying conventional learning at students class X SMAN 12 Padang.